The Role of Personality Traits, Knowledge Sharing, Informational-Normative Conformity, and Instrumental-Expressive Ties in Enhancing Employee Innovative Performance - Lestari, Jumaali Davit; Anjaningrum, Widiya Dewi; Cucio, Janice Soro (Universitas Negeri Malang, 2024)
All business sectors have recognized the importance of innovation in facing the challenges of technological disruption in the post-pandemic era. However, employee innovation performance must still be explored in the creative economy sector, especially the publishing subsector. This research is an effort to examine things that encourage the innovation performance of PT. Litera Media Tama and partners employees. A questionnaire collected data from all employees (n = 180). The research instrument was validated through the outer model test, and the hypothesis was tested through the inner model test using the SEM-PLS analysis. The research results show the partial mediating role of knowledge sharing on the influence of employee personality traits on employee innovation performance. Employee innovation performance is also significantly influenced by instrumental-expressive ties. Meanwhile, instrumental-expressive ties are also strongly influenced by informational-normative conformity. Further research is expected to relate each dimension of personality traits with knowledge sharing and employee innovative performance to determine which personality types are dominant, differentiate between permanent and freelance employees, and expand the research area. Keywords: Personality traits, Knowledge sharing, Work conformity, Social ties, Employee innovative performance